Analisis Suplai Beras Dan Proyeksinya Di Provinsi Aceh - Shafwan Fahmi; S Safrida; Suyanti Kasimin (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to determine the level of availability of grain production to fill the needs for a certain period of time and the continuity of grain supply to the availability of current paddy fields by taking secondary data, processing data analysis for modeling in projected harvest area, grain production, consumption and rice prices and then the rice production projection is carried out for 2018 until 2022. The results show that for the projections during 2018 to 2022 the rice harvest area will grow by 1.8% per year, rice productivity is 1.4% per year so it can be ensured that grain and rice production will grow by 3.2% per year with a predicted rice consumption growth rate of 1.7% per year from grain production of 2,494,613 tons and rice consumption of 594,145 tons in 2017 which indicates that Aceh Province will still experiencing a surplus of sa rice with the next 5 (five) years with a prediction of grain production of 2,923,845 tons, consumption of rice at 646,394 tons so that the surplus of rice is 1,185,693 tons in 2022. This condition will still occur if all variables are considered constant and the Government's efforts in providing and rehabilitation of agricultural facilities and infrastructure optimally